Perceptions of the impact of labour market flexibility on foreign direct investment in South Africa - Sompondo, Yolanda Lungelwa (My University, 2013)
Foreign Direct Investment (FDI) is said to have spill over effects such as skills transfer and employment creation. In 2011, FDI inflows into South Africa declined to -0.12% of GDP and 43.6% less in the first quarter of 2012, than the same time in the previous year. There are suggestions that the country’s labour regulations are one of the contributory factors in low FDI inflows. This can also be inferred from the Global Competitiveness Report, 2012-2013, on which the study is based. The report ranks labour regulations in South Africa as the second highest obstacle in doing business. The country is also ranked 143rd out of 144 countries in hiring and firing practices. The objective of this study was to explore how South African labour regulations are perceived to impact FDI. The study focused on perceptions of three economic stakeholders- business, government and labour. This study deployed qualitative methods using purposive sampling and an in-depth interview guide. The interviews were conducted face to face with a total of 23 interviewees from the three categories. The findings of the study revealed that while labour and government were found to differ on the perception of rigidity of labour regulations, all investors interviewed perceived South African regulations to be inflexible. The findings of business perceptions were categorised into two sections. The first section looked at costs and the second section looked at uncertainty. On the cost section, the study observed that non-wage costs were perceived to have increased due to difficulties in laying off employees that were not productive. Trade union conduct during protest actions and inefficient judiciary structures were also perceived to contribute to non-wage costs. Wage-costs were perceived to have increased by having to employ skilled BEE candidates who were considered costly as they were alleged to be in short supply. The second section suggested the legislative environment and policy formation were perceived by business stakeholders to be ii uncertain, consequently threatening confidence and deterring investment. The study also revealed varying perceptions among the three biggest union federations in the country. The National Council of Trade Unions (NACTU) and Federation of Unions of South Africa (FEDUSA) were more receptive to the relaxation of labour regulations and perceived current regulations as deterrent to business. The Congress of South African Trade Unions (COSATU) was against the relaxation of regulations and suggested regulations are currently flexible. The study revealed inconsistencies between various government departments in the application of its FDI policies. While other departments emphasised the need and importance of FDI, some departments highlighted the need for the protection of workers. However, government has adopted investor friendly policies in the National Development Plan which aims to create a business friendly environment. The study found this will create policy certainty and will be a step closer to such an environment. The recommendations of the study focus on ways of engagement among stakeholders. There needs to be better ways of resolving differences between the parties. Where violence is instigated, particularly by trade union members, the stakeholders need to work together to hold the responsible individuals accountable. This will promote an environment of lawfulness and therefore stability for FDI. The National Economic Development and Labour Council (NEDLAC) must be used to consolidate discrepancies in perceptions. Existing organisational weaknesses of this forum must be addressed in order to ensure that it serves its purpose- which is to promote robust discussions and reach amicable agreements which will enrich not only their interests but also those of the economy as a whole.
MBA thesis
Keywords: Labour market flexibility; Foreign direct investment